Características de adubos orgânicos, efeitos no solo e no desempenho da bananeira - Müller, Danielle Helena (2012)
This work aimed to evaluate the effect of different sources of organic fertilizers over yield and fruit quality of banana ‘grand Naine’ in the first production cycle, as well as to study fertilizers mineralization and their influence over soil chemical and microbiological properties. Sources of organic fertilizers were: plain cattle mature manure, plain poultry mature manure, swine waste water, cattle manure compost, cattle mature manure compost, poultry mature manure compost, swine mature manure compost. Amounts of each fertilizer were calculated based on recommended Nitrogen rates for the crop. Treatments efficiency on soil were evaluated by chemical and microbiological analysis and mineralization through incubation period. Effects on plants were measured through pseudostem diameter, height of blossoming insertion and leaves per plant at blossoming as well as crop cycle period. At post-harvest measurements were: bunch and second hand mass, number of hands and fruits per bunch, number of fruits in the second hand, length and diameter of these fruits. Fruit chemical analysis were: pH, soluble solids and titratable acidity. Experimental design was random blocks with four repetitions with four plants each. Independently of organic fertilizer type, it is possible to nourish and produce commercial standard ‘Grand Naine’ bananas and at the same time to improve soil characteristics, distinctly changing its chemical and microbiological attributes.